The Effects of Deformation on the Early Crystallization Kinetics of Basaltic Magmas - Tripoli, Barbara; Manga, Michael; Mayeux, Jerome; Barnard, Harold (Frontiers in Earth Science, 2019)
Crystals and bubbles nucleate and grow in a magma that experiences a range of temperatures, pressures and strain-rates. We have a good conceptual and sometimes quantitative understanding of how crystallization and bubble nucleation are controlled by decompression and cooling. Here we explore the effect of strain-rate on the crystallization kinetics of magmas. In order to understand the interaction between deformation and crystallization, samples of basalt were deformed during their crystallization. We made measurements at subliquidus conditions (1160°C) and deformed samples in compression at strain-rates varying from 0 to 2x10-4 s-1 for a total strain of 0.31. We simultaneously imaged the samples using X-ray micro-tomography. Under static conditions, there was no crystallization during the 260 minutes experiment. By increasing the strain-rate to 1.0x10-4 s-1, crystallization occurs. However, the crystallization kinetics in our experiment do not depend on the strain-rate. We hypothesize that deformation may have an effect on the parameters that govern the crystallization kinetics of magmas, such as activation energy and diffusion by changing chemical potentials.